2017
DOI: 10.1039/c6ra28232f
|View full text |Cite
|
Sign up to set email alerts
|

Si-centered capped trigonal prism ordering in liquid Pd82Si18 alloy study by first-principles calculations

Abstract: Distribution of trigonal prism capped with three half-octahedra (orange clusters), archimedean anti-prism (green ones) and icosahedron (blue ones) clusters in Pd82Si18 at different temperature (a) 900 K, (b) 1216 K. (c) Connection way of different clusters, and pink ones are the sharing atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Whereas the | ( )| for Fe follows the expected exponential decay quite well with a single sinusoidal oscillation, the | ( )| for Pd82Si18 deviates significantly from the expected line, indicating the presence of multiple components of oscillation. It is possible that the strong short-range order around Si because of covalent Pd-Si bond [22,23] is biasing the density correlations. The theory by Ornstein and Zernike presumes spherical interatomic potentials [12].…”
Section: S(q1) -1 and The Wl/wg Ratio Can Be Considered As The Idealimentioning
confidence: 99%
“…Whereas the | ( )| for Fe follows the expected exponential decay quite well with a single sinusoidal oscillation, the | ( )| for Pd82Si18 deviates significantly from the expected line, indicating the presence of multiple components of oscillation. It is possible that the strong short-range order around Si because of covalent Pd-Si bond [22,23] is biasing the density correlations. The theory by Ornstein and Zernike presumes spherical interatomic potentials [12].…”
Section: S(q1) -1 and The Wl/wg Ratio Can Be Considered As The Idealimentioning
confidence: 99%
“…The PBE-DFT method is accurate for depicting the atomic interaction in Pd-Si system which has been validated in Refs. [45,46]. Only the point is utilized to sample the Brillouin zone and the default energy cutoffs of 251 eV are employed.…”
Section: A Datasets For Machine Learning Training and Validationmentioning
confidence: 99%
“…However, for the Si-centered clusters in both systems, the fraction of the Z9 motif is larger than 15% with respect to the total Si-centered clusters at 800 K from AIMD or the NNP. It should be noted that the Si-centered Z9 cluster is often referred to as a trigonal prism capped with three half octahedra [46,52], which is a "crystal gene" in Pd 3 Si crystalline phase. Figures 5 and 6 show the RMSEs in the energies and forces for the undistorted and distorted crystal structures of Pd 3 Si and Pd 9 Si 2 compositions in the training set and validating set, respectively (see Computational Methods above) when comparing the NNP results with respect to the DFT results.…”
Section: A Performance Of the Nnp For Liquid Structuresmentioning
confidence: 99%
“…9 Pd-Cu-Si, one of the first bulk metallic glasses developed in 1974 by Chen et al, was often selected for scientific investigation in the common composition Pd 77.5 Cu 6 Si 16.5 , 10-13 but systematic study on the effect of different Cu addition on the glass formation is still limited. In this case, the binary alloy series Pd 81+x Si 19-x (x=0, 1, 1.5, 2, 2.5, 3, 4) and the ternary alloy series Pd 83.5-x Cu x Si 16.5 (x=0, 2,4,6,8,10,12) were selected to investigate the effect of Cu additions on the glass forming ability (GFA) and thermal stability in the binary Pd-Si system. First, a combination of X-ray diffraction (XRD), transmission electronic microscopy (TEM) and differential scanning calorimetry (DSC) was used to investigate the amorphous state of the produced samples.…”
Section: Introductionmentioning
confidence: 99%
“…This may contribute to the unique structure around the eutectic composition or the sharp T 0 curve on the Pd rich side. Recently, First-principles molecular dynamic (MD) simulations and Monte Carlo simulations were done on the eutectic composition (Pd 82 Si 18 ) 4 and the hyper-eutectic composition (Pd 81 Si 19 , Pd 80 Si 20 ). 5,6 It has revealed that the important role of atomic clusters, short-range order (SRO), topological structures in the formation of Pd-Si metallic glass and the complexity of the local structure around the eutectic point.…”
Section: Introductionmentioning
confidence: 99%